Fasilitas Peralatan dan Sumber Daya Manusia (SDM) Terhadap Keamanan Bandar Udara Ahmad Yani Semarang - Juanda Siahaan (Research and Development Agency of The Ministry of Transportation, 2011)
The success of airport operators in providing services to passengers is closely related to the provision of security for passengers. It has to be a major concern for every airport operator because airport security is a process to provide aviation safety. There are several things that have to be considered in creating quality and quantity of security equipments including security facilities and human resources as well. Aviation security personnel consist of 52% core personnel (employees of PT Angkasa pura), of outsourcing personnel and 37% of army personnel.